2002
DOI: 10.1165/ajrcmb.26.4.4473
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Elastase Induces MUC5AC Gene Expression in Airway Epithelium via a Pathway Involving Reactive Oxygen Species

Abstract: Neutrophil-predominant airway inflammation and mucus obstruction of the airways are major pathologic features of chronic airway diseases, including cystic fibrosis and chronic bronchitis. Neutrophils release elastase, a serine protease that impairs mucociliary clearance and stimulates goblet cell metaplasia and mucin production. We previously reported that neutrophil elastase increases expression of a major respiratory mucin gene, MUC5AC, by enhancing mRNA stability. However, the molecular mechanisms of elasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 37 publications
7
121
0
1
Order By: Relevance
“…It has been previously documented that ROS may alter the expression of certain genes by interfering with message stability (75)(76)(77)(78). Our present data provide evidence that the irondependent generation of ROS indeed coincided with a decrease in the stability of elastin mRNA (Figs.…”
Section: Discussionsupporting
confidence: 80%
“…It has been previously documented that ROS may alter the expression of certain genes by interfering with message stability (75)(76)(77)(78). Our present data provide evidence that the irondependent generation of ROS indeed coincided with a decrease in the stability of elastin mRNA (Figs.…”
Section: Discussionsupporting
confidence: 80%
“…NE stimulates translocation of PKCδ to the plasma membrane, resulting in activation of dual oxidase 1 (DUOX1 (Shao and Nadel, 2005a) and subsequent activation of TNFα-converting enzyme (TACE) to cleave and release the EGFR ligand, TGFα, permitting activation of EGFR and down-stream signaling via RAS-Raf-MEK1/2-ERK1/2 and either NF-κB (Song et al, 2005) or Sp1 (Perrais et al, 2002) activation. We and others have shown that NE also induces oxidant signaling in airway epithelial cells (Aoshiba et al, 2001, Fischer and Voynow, 2002 and these oxidants are required for increased MUC5AC expression. We have recently reported that NE upregulates a cytoplasmic oxidoreductase, NADPH quinone oxidoreductase 1 that is required for NE-induced lipid peroxidation and for NE-regulated MUC5AC mRNA expression .…”
Section: Neutrophil Elastase and Mucins Mucus Secretion And Mucocilmentioning
confidence: 69%
“…This effect was recently found to occur via a proteolytic activation of epidermal growth factor receptor signalling cascade involving TGF-a [28]. An additional mechanism involving reactive oxygen species has been put forward [29]. Since DBA/2 mice are sensitive to oxidants, have normal BALF EIC values and do not develop significant GCM, it can be assumed that the proteolytic pathway of MUC5AC activation is more relevant under the experimental conditions of the current study.…”
Section: Discussionmentioning
confidence: 81%